The Role Of Christian Religious Education In Developing 21st Century Skills In Church Youth - Sianturi, Ruth; Romika, Romika (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This article examines the role of Christian Religious Education (PAK) in developing 21st century skills among church youth. In an era of constant change, where technology and globalization affect all aspects of life, PAK not only focuses on teaching spiritual and moral values, but also supports the development of skills such as critical thinking, collaboration, effective communication and creativity. This research uses a qualitative descriptive approach, with a focus on literature study. By using this method, research emphasizes the importance of using literature to understand best practices and theories that support the integration of 21st century skills in the context of religious education, thereby enabling church youth to be more adaptive and innovative in dealing with social and technological problems. . dynamics. The results of this research through an integrated approach between theology and practical skills, PAK seeks to equip the younger generation with the tools necessary to succeed and contribute positively in modern society. This article discusses how PAK's curriculum and teaching methods can be adapted to be more relevant to the needs of church youth, preparing them to become leaders and bringers of change in the future. The conclusion from conducting this research is that in facing the challenges of the 21st century, Christian Religious Education (PAK) plays an important role in equipping the young generation of the church with skills that not only support their spiritual growth but also prepare them to become competent and empathetic world citizens.